KARAKTERISASI ELEKTRODA SELEKTIF ION (ESI) KADMIUM TIPE KAWAT TERLAPIS BERMEMBRAN D2EHPA - Kusrini, Endah; Atikah, Atikah; Sulisyarti, Hermin (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABStract Determination of the basic characters of coated wire cadmium ion selective electrode (Cd CWE) which have performed include Nernst factor, linear concentration range, limit of detection, response time and life time. Potensial measurements were performed using optimum membrane composition comprising active ingredients of Di(2-Ethyl Hexyl)Phosporic Acid (D2EHPA) : Polyvinylchloride (PVC) : Di-butyl Pthalate (DBP) with % w/w ratio 16:28:56 dissolved in tetrahydrofuran (THF) at ratio of 1:3 (w / v) in the test solution of CdCl2 1x10-8 - 1x10-1 M at pH 5 and optimum soaking time of 20 minutes. The result showed that Cd(II) CWE is being made demonstrated Nernstian with Nernts factor of 27.7±0.267  mV / decade of cadmium(II) at linear concentration range from 1x10-5 to 1x10-1 M or 1.46 to 14600 ppm, detection limit of 6.607 x10-6 M or 0.317 ppm, response time of 40 seconds and life time of 42 days. Reproducibility production of 3 Cd(II) CWE is well shown by the price of a standard deviation (SD) and coefficient of variation (CV) were respectively 0.264 and 0.953%.   Key words: characterization, D2EHPA, ESI cadmium, membrane coated wire